PEMBANGUNAN SERVER APLIKASI PENJADWALAN KULIAH BERBASIS MOBILE DI STMIK KRISTEN NEUMANN INDONESIA - Jenni Veronika Br Ginting; Rapita Sari Br Sembiring (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2017)
Scheduling is the allocation of resources within the range specified time to complete a set of tasks. Scheduling is very important to design and manage a system consisting of a number of activitieswith limited resources. Along with a high mobility rate, the last few years the booming mobile devices or mobile devices, mobile devices are the most rapidly is Mobile where almost everyone has it will be built Server Application Scheduling Lecture-Based Mobile where the data schedules and schedule changes can be collected or stored in a computerized data base. This server development using MySql database server. This server can connect with Class-Based Mobile Application Scheduling.